CRITERIA FOR DEFINING MOODS OF THE VERB IN UZBEK AND TURKISH LINGUISTICS - Zilola XUDAYBERGENOVA (Uluslararası Türk Lehçe Araştırmaları Dergisi, 2019)
In the Uzbek and Turkish languages, moods of the verb is one of the main categories. The purpose of the article is a comparative study of the mood of verbs - verb forms, which is expressing the modal attitude of the speakers of these languages to objective reality. After all, this issue was not the subject of a separate study. The verb moods in the compared languages have common and similar grammatical affixes, however, there are also verb moods that do not exist in a comparable second language. There are different approaches to the classification and study of verb moods in Uzbek and Turkish linguistics. At the same time, various scientific sources describe various classifications of moods of verbs in Turkish linguistics and Uzbek linguistics. The article analyzes the differences and similarities between the moods of verbs and their interpretations in Uzbek and Turkish linguistics. The article notes that in Uzbek and Turkish linguistics, the indicative mood contradicts other moods of verbs. As a result, it is recognized that in the languages being compared there is no single approach to the relationship between the category of tenses and the mood of verbs, their classification and types, they even express completely different opinions about the same form of the verb. As a result of the analysis of examples, it is proposed to use the degrees of objectivity and subjectivity as criteria for differentiating the moods of verbs and tenses.